Correction: Direct determination of 3-chloro-1, 2-propanediol esters in beef flavoring products by ultra-performance liquid chromatography tandem quadrupole mass spectrometry. Issue 6 (4th January 2017) - Chai, Qingqing; Zhang, Xiaoming; Karangwa, Eric; Dai, Qingyuan; Xia, Shuqin; Yu, Jingyang; Gao, Yahui
Abstract : Correction for 'Direct determination of 3-chloro-1, 2-propanediol esters in beef flavoring products by ultra-performance liquid chromatography tandem quadrupole mass spectrometry' by Qingqing Chai et al., RSC Adv., 2016, 6, 113576–113582.